Optimal maximum benefit model and prediction of carbon sequestration: A case study of the Greater Khingan Mountains - Wei Liu; Kehui Wu (Energy Reports, 2023)
In order to make better use of the value of forest carbon sequestration and other aspects, this paper reformulate the forest management plan including deforestation in addition to the current conventional forest management plan. Moreover, we take into account the carbon sequestration benefits of forest products, analyze and predict the carbon sequestration amount of forests and forest products over time, and the deforestation amount including environmental damage and economic benefits, and put forward some reasonable suggestions based on the results achieved.In order to discuss the applicability of the model, we apply the model to the Greater Khingan Range to predict the carbon sequestration of the entire forest and its forest products 100 years from now, and to explore the best management options for the Greater Khingan Mountains. The result we obtain is that the final total carbon sequestration of Greater Khingan Range and their forest products is 2,461,259,714.52 tons after 100 years. Meanwhile, on the reasonable assumption that the Greater Khingan Mountains consist of only two kinds of trees, each time 0.8904% of the area of pine trees is cut, giving the forest 0.5 years of recovery time; by cutting 0.2326% of Betula platyphylla area at a time, with an interval of 0.8 years for recovery, best management is achieved.